Citizenship and identity - Isin, Engin F. (Engin Fahri) 1959- (Politics and culture., 1999)
Through a detailed introductory discussion of the relation between the civil and the political, and between recognition and representation, this book provides a comprehensive vocabulary for understanding citizenship. It uses the work of T H Marshall to frame the critical interrogation of how ethnic, technological, ecological, cosmopolitan, sexual and cultural rights relate to citizenship.